A proteomics approach to identifying key protein targets involved in VEGF inhibitor mediated attenuation of bleomycin‐induced pulmonary fibrosis. Issue 1 (24th November 2015) - Kulkarni, Yogesh M.; Dutta, Sucharita; Iyer, Anand Krishnan V.; Venkatadri, Rajkumar; Kaushik, Vivek; Ramesh, Vani; Wright, Clayton A.; Semmes, Oliver John; Yakisich, Juan S.; Azad, Neelam
Abstract : Idiopathic pulmonary fibrosis (IPF) is a progressive lung disease with a life expectancy of less than 5 years post diagnosis for most patients. Poor molecular characterization of IPF has led to insufficient understanding of the pathogenesis of the disease, resulting in lack of effective therapies. In this study, we have integrated a label‐free LC‐MS based approach with systems biology to identify signaling pathways and regulatory nodes within protein interaction networks that govern phenotypic changes that may lead to IPF. Ingenuity Pathway Analysis of proteins modulated in response to bleomycin treatment identified PI3K/Akt and Wnt signaling as the most significant profibrotic pathways. Similar analysis of proteins modulated in response to vascular endothelial growth factor (VEGF) inhibitor (CBO‐P11) treatment identified natural killer cell signaling and PTEN signaling as the most significant antifibrotic pathways. Mechanistic/mammalian target of rapamycin (mTOR) and extracellular signal‐regulated kinase (ERK) were identified to be key mediators of pro‐ and antifibrotic response, where bleomycin (BLM) treatment resulted in increased expression and VEGF inhibitor treatment attenuated expression of mTOR and ERK. Using a BLM mouse model of pulmonary fibrosis and VEGF inhibitor CBO‐P11 as a therapeutic measure, we identified a comprehensive set of signaling pathways and proteins that contribute to the pathogenesis of pulmonary fibrosis that can be targeted for therapy against this fatal disease.